Mex3a promoter hypomethylation can be utilized to diagnose HBV-associated hepatocellular carcinoma: a randomized controlled trial - Yang, Jie-Ru; Tian, Yu-Xin; Li, Jin-E.; Zhang, Ying; Fan, Yu-Chen; Wang, Kai (Frontiers in Pharmacology, 2024)
Background: Hepatocellular carcinoma remains a humanity health challenge. Therefore, there is an urgent need to develop novel biomarkers with high efficiency yet fast ability to meet the requirements of Hepatocellular carcinoma treatment.The 229 patients with HBV-associated hepatocellular carcinoma (HCC), 298 patients with chronic hepatitis B (CHB) and 96 healthy controls were retrospectively analyzed. Methylation levels of the Mex3a promoter in peripheral blood mononuclear cells (PBMC) were measured by methylight to obtain clinical and laboratory parameters.The Mex3a promoter methylation level in HCC patients (median 0.289%, interquartile range 0.126-0.590%) was significantly lower than that in CHB patients (median 0.999%, interquartile range 0.417-1.268%; P<0.001) and healthy people (median 2.172%, interquartile range 1.225-3.098%; P<0.001). The Mex3a mRNA levels in HCC patients (median 12.198, interquartile range 3.112-18.996) were significantly higher than those in CHB patients (median 1.623, interquartile range 0.066-6.000; P<0.001) and healthy controls (median 0.329, interquartile range 0.031-1.547; P<0.001).Methylight data is expressed as a percentage of methylation reference value (PMR). The Mex3a PMR value was negatively correlated with mRNA expression level (spearman's R=-0.829, P<0.001). The Mex3a PMR value of HCC patients was significantly correlated with age (Spearman's R=0.113, P=0.044), and mRNA level was significantly correlated with ALT (Spearman's R=0.132, P=0.046).The Mex3a promoter methylation levels and mRNA levels are also independent factors in the development of liver cancer. The Mex3a promoter methylation and mRNA levels were better at distinguishing HCC from CHB than AFP [area under the receiver operating characteristic curve (AUC) for predicting HCC vs. CHB: 0.915 vs. 0.715, P<0.001]. The combined use of AFP and Mex3a methylation levels and mRNA levels further improved the area under the receptor working characteristic curve.The presence of Mex3a promoter hypomethylation in hepatocellular carcinoma can be used as a non-invasive biomarker to detect early liver cancer.